Student-Athletes’ Narratives of English Learning Needs in Special Sports Classes: Implications for Contextual ESP Instruction - Khairunnisa Nasution; Joko Priyana (Yayasan Adra Karima Hubbi, 2026)
Background. Student-athletes in special sports classes represent a unique group with dual demands in academic learning and intensive athletic training. Limited study time, physical fatigue, and the need for international communication in sports make their English learning needs distinct and academically important to investigate. However, these specific needs are often not adequately addressed in conventional English classrooms. Purpose. This study aims to analyze the English learning needs of junior high school student-athletes to inform more contextual and relevant ESP instruction. Method. This study employed a descriptive quantitative design involving 58 student-athletes. Data were collected through a needs analysis questionnaire focusing on target needs and learning needs. The analysis highlights students’ perspectives, preferences, and learning challenges as a basis for identifying effective instructional strategies. Results. The findings reveal that students prioritize speaking skills as the most essential for their future athletic communication, followed by listening skills. Students expressed a preference for interactive and engaging learning media such as games and videos, reflecting their need for dynamic and practice-oriented activities. Most participants identified themselves at an elementary level of English proficiency, with key difficulties in vocabulary, pronunciation, and fluency. In addition, students showed a strong preference for kinaesthetic learning styles and outdoor learning environments, indicating the importance of movement-based and experiential learning. These findings reflect student voices and learning experiences that emphasize the need for more engaging and context-relevant instruction. Conclusion. The study concludes that English instruction for student-athletes should be designed using contextual, communicative, and multisensory approaches that align with their lived learning experiences. These findings provide practical implications for developing ESP-based materials and strategies that support both academic development and athletic performance.